Wireless building automation devices supporting multiple standards: Challenges and feasibility - Bag, Gargi; Zhibo Pang; Johansson, Morgan E.; Xiaoyu Min; Shaoling Zhu (IEEE Conference on Industrial Electronics and Applications (Online), 2016)
Buildings will be more and more automated in future to cater for user's comfort, security and energy efficiency needs. Most of the building automation devices are expected to be in operation for a number of years. However in future, markets will be shared by a number of communication standard, which implies that the user may want to upgrade their device to another communication standard easily without having to discard the device. Right now such a flexibility is not provided. This paper proposes to utilize the most recently available chipset which support multiple wireless standard using the same hardware and can be easily switch between the standards if required. It then provides a detailed experimental evaluation of the chipset to determine the chipset's performance in terms of round trip time, packet delivery rate and coverage.